Analisis Teknologi Switching Menggunakan Topologi Mesh - Nadita Dwi Pramestia; Sabda Dwi Arvinda; Ade Sudrajat; Naufal Cahyo Widodo; Didik Aribowo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Nowadays, many people use technology in the form of cellphones to share data, be it images, sound, video, text, and some of them. The speed of sending data depends on how fast the system manages it, if there is damage or obstacles then most likely the data will not be sent, therefore there must be someone who manages the system so that there are no obstacles when sending data. Mesh topology is a simulation that is connected to each other to send data from one computer to anothe computer, from the simulation we can see whether there are obstacles in sending data or not. The purpose of this research is to compare mesh topology and switching technology in data transmission simulation. This research uses library research methods to collect information and scientific works, namely literature related to literature review.